(untitled) (Journal of Creative Industry and Sustainable Culture, 2023)
The most common garments made by customers utilizing existing batik fabric are traditional baju kurung and modern baju kurung. However, difficulties have occurred in adjusting to the fact that there is excess and waste of batik fabric happens throughout the process of arranging and cutting pattern designs. In addition, there is also a situation where the arrangement of the motif is not balanced on the clothing pattern and it also cause the batik motif being cut and not joined when sewing. Besides that, there is a lot of excess batik fabric if the user is a small size such as S and M size, because of that, there is a waste of fabric on the existing batik fabric. Meanwhile, occasionally the batik fabric is insufficient for large sizes such as L and XL, necessitating the addition of more fabric to complete a garment. The purpose of this study is to identify the visual observation analysis of the pattern grading arrangement layout of women’s traditional baju kurung on existing batik fabric. The experiment of visual observation was employed as a data collection method for this investigation. This experiment created pattern measurement calculation, pattern arrangement, and visual illustration of women’s traditional baju kurung utilizing existing batik fabric. The study’s findings indicate that existing batik fabric should be evolved into a new pattern grading arrangement that adheres to modern techniques and technology while minimizing the quantity of extra fabric discarded.